The Use Of Numbered Heads Together (Nht) Method To Improve Student’s Writing Recount Text At First Grade Students Of MA Darul Aminin NW Aikmual In Academic Year 2014/2015 - Suparlan Suparlan (Lembaga Penelitian dan Pendidikan Mandala, 2019)
This study is purpose to find out the use of numbered heads together (NHT) method to improve student’s writing recount text at first grade student of MA Darul Aminin NW Aikmal in academic year 2014/2015. There were 35 students of MA Darul Aminin NW Aikmual as the subject of the study. The type of this study was classroom action research. This action study was done in two cycles. Each cycle consist of four steps; Planning, Acting, Observing, and Reflecting. The data gathering used observation table check list and field note to obtain information about teacher, the student’s activities and performance during the implementation of NHT method and quantitative data was gained from student’s result writing test. The data analyzed use qualitative and quantitative approach. Based on the data analyzed was gotten that first, the students’ ability in writing recount texts could be improved by using NHT method. Before the study was done, the mean score of students from 50.14 to 75.31 with percentage (25.71%) to (78.12%) is higher than criteria minimum (KKM). The students got score up than 70 there were 25 students with percentage 78.12%. Second, the students’ activeness increased from cycle 1 to cycle 2. Finally, it can be taken conclusion that there was the significant effect of Number heads Together (NHT) method to increase the students’ writing ability in recount text at first grade student of MA Darul Aminin NW in academic year 2014/2015.